2017
DOI: 10.1007/s12544-017-0269-1
|View full text |Cite
|
Sign up to set email alerts
|

Equity in transport: Learning from the policy domains of housing, health care and education

Abstract: Introduction The aim of this paper is to explore the equity principles in three main domains of government intervention (health, education and especially housing) and to draw lessons for the domain of transport. In line with the burgeoning literature, we consider equity in transport to be primarily -albeit not only -concerned with the level of accessibility conferred by the transport-land use system to persons. While some (recent) research has explored what requirements of fairness may imply for accessibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Although health, education, and housing have established equity principles, fairness in access has only recently received attention in transportation (2). As such, there is not a universally adopted methodology for assessing transportation equity (1).…”
Section: Transportation Modeling and Equitymentioning
confidence: 99%
“…Although health, education, and housing have established equity principles, fairness in access has only recently received attention in transportation (2). As such, there is not a universally adopted methodology for assessing transportation equity (1).…”
Section: Transportation Modeling and Equitymentioning
confidence: 99%
“…Further, together with an increasing interest in critical perspectives in transport, a specific attention has risen around issues of justice and equity. Research on transport justice is primarily based on recognizing the transport system's pivotal role in guaranteeing or hindering access to crucial opportunities and, thereby, delivering equity in all welfare domains (such as health, education and housing) (Jeekel & Martens, 2017). Some scholars (Enright, 2019;Sheller, 2018;Verlinghieri & Schwanen, 2020) have indicated that research on justice in transport planning mainly draws upon distributive approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Mobility is an important component of social participation and integration. It allows access to employment, education, and social networksin total, to modern life and societal opportunities [1][2][3]. Digitalisation can have a substituting effect: Internet and mobile devices allow home office solutions for a number of jobs.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the share of immigrants strongly differs between 7% in Vogelsberg, in the northern part of the region, to almost 35% in Offenbach, which is located in the heart of the metropolitan region. However, different groups of immigrants have to be differentiated: (1) people with immigrant background, which covers all people who either have immigrated themselves or have at least an immigrated parent, and (2) immigrants, which describes people who have immigrated themselves. For the second group, motivation can be very different, such as employment, political instability due to wars, poverty, social reasons, education, and many more.…”
Section: Introductionmentioning
confidence: 99%